Pelatihan Teknik Presentasi Ilmiah yang Efektif Bagi Mahasiswa Biologi FMIPA UNM - Dian Dwi Putri Ulan Sari Patongai; Halifah Pagarra; Saparuddin; Sahribulan; Rosdiana Ngitung (Ininnawa : Jurnal Pengabdian Masyarakat, 2023)
The skill of making scientific presentations is a skill that must be mastered by current students, especially final year students who will soon be preparing their final project. The problem with Biology students as partners in this service is the lack of student ability to make effective scientific presentations. Preliminary analysis showed that 41% of students found it very difficult to present properly. The solution offered is to hold effective scientific presentation training with the aim of providing understanding and training students' skills in making scientific presentations and making good presentation media. The implementation of this training consists of 3 sessions namely material delivery sessions, independent work and simulations. The results achieved in this training activity are an increase in the participants' knowledge and skills in making presentation materials and presenting them in an effective presentation. In terms of participant satisfaction, it shows that this community service has an average score of 3.89 with very good/very satisfied criteria. .